Development of Teaching Methods Using Infographic Media and Comic Life Practice Towards Students Learning Interests - Mansyur; Ahmad Rudi; Akbar Iskandar (Ceddi Journal of Education, 2022)
The purpose of the study was to determine the process of developing teaching methods using infographic and comic life media on interest in learning chemistry, teaching methods using infographic media and comic life on interest in learning chemistry can be declared valid, practical and effective for use in schools. This type of research is development research. The data analysis technique used to obtain the appropriate data, so that it can be processed using the data technique validation results of the infographic and comic life media teaching methods. Data on the effectiveness of learning media, data on the practicality of learning devices. The procedure for developing teaching methods includes needs analysis, design phase, realization/construction phase, test and evaluation phase and implementation phase. Development results in the form of teaching methods based on infographics and comic life that can be used by teachers and students in the learning process. In the expert test of instrument validation, the teaching method underwent several revisions before being implemented in schools until a valid, effective and practical learning media was obtained. The results of the validation of infographic and comic life media with an average validity value of 4.0. The practicality of teaching methods meets the criteria by providing convenience for educators/teachers and students in the learning process and the effectiveness of teaching methods meets the criteria by looking at the positive responses of students with a percentage of 70% stating strongly agree and 30% agreeing.